THE INFLUENCE OF WORK MOTIVATION TOWARD THE LIBRARIAN'S PERFORMANCE IN UPT LIBRARY OF UNIVERSITAS HASANUDDIN MAKASSAR - Asniati, Asniati; Ahmad, La Ode Ismail; Tike, Arifuddin (Program Pascasarjana, UIN Alauddin Makassar, 2021)
The main problem of this study is how can the work motivation influence the librarian performance in UPT Library of Universitas Hasanuddin Makassar. Then, this problem is broken down into some sub-problems or research questions, such as 1) how is the work motivation in UPT Library of Universitas Hasanuddin Makassar, 2) how is the librarian performance in UPT library of Universitas Hasanuddin Makassar, and 3) how much is the influence of work motivation toward the librarian performance in UPT library of Universitas Hasanuddin Makassar. This study employed descriptive statistical research with a quantitative approach. The population of this study is all the librarians in UPT library of Universitas Hasanuddin Makassar, with a total number of 33 librarians who became the respondents. The procedure of collecting data in this study used a printed questionnaire. Then, the technique of data analysis was done by using correlation and validity test. This study aims to know about the influence of work motivation toward librarian performance in UPT library of Universitas Hasanuddin Makassar. Based on the result of the data, the variable of work motivation (X) had a strong influence on librarian performance (Y) in UPT library of Universitas Hasanuddin Makassar, the value of pearson correlation was 0,667 or 66.7%, then the significance was 0,000 < 0,05. These values showed that the variable of work motivation (X) influence the librarian performance (Y) simultaneously in 45%. Meanwhile, the leftover in 55% was influenced by other variables. The implication of this study is that the other researchers will take the topic of work motivation toward librarian performance into account and observe it deeply to measure how much is the librarian performance can improve the capacity of library's visitor, which depends on how much motivation that can be given from head of librarian which can affect the prosperity of the librarians.